Electromagnetic form-factor of vector mesons in the relativistic quark model - Andreev, Viktor V.; Haurysh, Vadzim Yu. (Journal of the Belarusian State University. Physics, 2019)
In paper studied the behavior of electromagnetic form-factors of the V → Pl+l- transitions for vector V and pseudoscalar P mesons within the framework of the relativistic quark model, based on the point form of Poincaré-invariant quantum mechanics. Based on the self-consistent description of the lepton and radiative decay constants of pseudoscalar and vector mesons, the behavior of the form-factors, depending on the transmitted momentum, for the ω → π0l+l- and φ → ηl+l- processes is obtained. Thenumerical results within the framework of the proposed model are compared with modern experimental data. Shown, that the behavior of form-factors is in good agreement with experiment. Acomparative analysis of the results obtained in different forms of Poincaré-invariant quantum mechanics will allow to research the role of various approximations often used in calculations and in practice, and also check the unitary equivalence of the different forms of dynamics.